Impact of multimodal strategies to reduce multidrug‐resistant organisms in surgical intensive care units: Knowledge, practices and transmission: A quasi‐experimental study - Nongyao Kasatpibal; Kaweesak Chittawatanarat; Nantana Nunngam; Daranee Kampeerapanya; Nongnut Duangsoy; Chanban Rachakom; Ubonrat Soison; Anucha Apisarnthanarak (Wiley, 2021)
Abstract Aim This study examined the effects of multimodal strategies on knowledge and practices in preventing multidrug‐resistant organism (MDRO) transmission among healthcare personnel (HCP), and to investigate MDRO transmission in two surgical intensive care units (SICUs). Design A quasi‐experimental study with a one‐group pretest-posttest design. Methods We recruited 62 HCP. Data were collected during 2017-2019. Multimodal strategies, including training, educational and reminder posters, an educational YouTube channel, champions and feedback, were used to enhance knowledge and practices. Data were analysed using Wilcoxon signed‐rank test and chi‐square test. Results After the intervention, median knowledge scores increased from 16.0 to 17.0 (p = .001), and overall correct MDRO prevention practices increased from 76.6% to 94.0% (p < .001). The MDRO transmission rate decreased from 25% to 0% (p < .001). Conclusion The findings indicate that multimodal strategies could enhance knowledge and practices for preventing MDRO transmission among HCP and could reduce the MDRO transmission rate in SICUs.